SERVICE QUALITY MEDIATION EFFECT OF ENTREPRENEURIAL ORIENTATION, AND LEARNING ORIENTATION, ON THE PERFORMANCE OF STARS HOTELS IN EAST KALIMANTAN - Yudhyani, Eka (Archives of Business Research, 2020)
This study aims to prove and analyze service quality as a mediating variable of the influence of entrepreneurial orientation, and learning orientation on the performance of star hotels in East Kalimantan. The results of research and testing using PLS with the SmartPLS v.3 program show (1) Entrepreneurial orientation has no signifikan effect on service quality.(2) Learning orientation has a positive and significant effect on service quality.(3) Entrepreneurial orientation has a positive and significant effect on hotel performance. (4) Learning orientation has no significant effect on hotel performance.(5)Sevice quality has a positive and significant effect on hotel performance This study was conducted to test the model of the effect of entrepreneurial orientation, and learning orientation on service quality and hotel performance and the result show that the model developed in this study is acceptable, meaning that the model in this study can be used as a model to improve performance star hotel in East Kalimantan.